2013
DOI: 10.1111/jac.12016
|View full text |Cite
|
Sign up to set email alerts
|

Legume Production and Irrigation Strategies in the Aral Sea Basin: Yield, Yield Components, Water Relations and Crop Development of Common Bean (Phaseolus vulgaris L.) and Mungbean (Vigna radiata (L.) Wilczek)

Abstract: With world population expected to reach 9.2 billion people by 2050, improved irrigation methods will be needed to increase the productivity of agricultural land and improve food supply worldwide. The objective of this work was to examine the effect of regulated deficit irrigation (RDI) and alternate furrow irrigation (AFI) on the yield and yield components of two legume species (common bean and mungbean) produced as a second crop following winter wheat in Uzbekistan, Central Asia. Water relations and crop deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 39 publications
(69 reference statements)
2
5
0
Order By: Relevance
“…In the rainfed-only cropping systems which are widely adopted in semi-arid and tropical regions, common bean productivity can be severely restricted to levels which are 50% below what could be achieved without water deficit [89][90][91][92]. The harmful effects of water deficit on grain yield were also reported in several other studies [82,[93][94][95][96][97][98], where reduced irrigation also lowered yield and yield components. Additionally, limited water availability (i.e., soil moisture levels) due to high levels of evaporation also negatively impacts yield components [10], fresh pod [7,9] or grain yields [8,99].…”
Section: Irrigationmentioning
confidence: 78%
“…In the rainfed-only cropping systems which are widely adopted in semi-arid and tropical regions, common bean productivity can be severely restricted to levels which are 50% below what could be achieved without water deficit [89][90][91][92]. The harmful effects of water deficit on grain yield were also reported in several other studies [82,[93][94][95][96][97][98], where reduced irrigation also lowered yield and yield components. Additionally, limited water availability (i.e., soil moisture levels) due to high levels of evaporation also negatively impacts yield components [10], fresh pod [7,9] or grain yields [8,99].…”
Section: Irrigationmentioning
confidence: 78%
“…But, further increment in irrigation frequency did not show significant variation in the parameter [Table 4]. Bourgault et al (2013) [17] also reported improvement in harvest index with increase in soil moisture.…”
Section: Yield and Yield Components Pod Number Per Plantmentioning
confidence: 99%
“…Common bean (Phaseolus vulgaris L.) has always faced numerous limitations and problems. Only 7 % of the total land dedicated to beans plantation globally has sufficient water, and 60 % of beans agriculture is carried out under intense drought stress conditions (Bourgault et al,2013). Due to absorption of more food and water from the soil, the plants with Mycorrhiza symbiosis have better growth and yield and have better resistance against environmental stresses (Haghighatnia et al,2013).…”
Section: Introductionmentioning
confidence: 99%